1953
DOI: 10.1111/j.1445-2197.1953.tb05016.x
|View full text |Cite
|
Sign up to set email alerts
|

The Vagal Body and Its Tumour

Abstract: To a philosopher, no circumstance, however trifling, INCE the first recognition of the carotid S body by von Haller in 1743, a number of other small masses of similar tissue has been described and the known branohial glomera or, as they are commonly described to-day, non-chromaffin paraganglia may be enumerated thus :2. The vagal bodyparaganglion juxtaor intra-vagale-situated in, or in juxtaposition with, the vagus nerve at the level of, or immediately below, the ganglion nodosum. The carotid body.4. The aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1955
1955
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The most inferior localization reported by this author was 2.0 cm below the lower border of the inferior vagal ganglion. In each of the 4 temporal bones sectioned through the superior vagal ganglion, Birrel (1953) found vagal bodies in the adventitia of the jugular bulb and within the ganglion itself. Among sensory ganglia, vagal ganglia are unique in containing paraganglionic tissue.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The most inferior localization reported by this author was 2.0 cm below the lower border of the inferior vagal ganglion. In each of the 4 temporal bones sectioned through the superior vagal ganglion, Birrel (1953) found vagal bodies in the adventitia of the jugular bulb and within the ganglion itself. Among sensory ganglia, vagal ganglia are unique in containing paraganglionic tissue.…”
Section: Discussionmentioning
confidence: 94%
“…In humans, vagal glomi have been recognized in the superior and inferior vagal ganglia and within or adjacent to the first centimeters of the nerve trunk immediately distal to the inferior ganglion (White, 1935;Lattes, 1950; Set0 et al, 1950;Hermann, 1951;Watzka and Scharf, 1951;Birrel, 1953; Lack, 1978). The description of a few vagal paraganglioma inferior to the carotid bifurcation in humans (Marcuse and Chamberlin, 1956;Jernstrom and Fry, 1957;Carey and Bradley, 1963) raises the question of a more extensive distribution along this nerve.…”
Section: Introductionmentioning
confidence: 99%
“…5 Stout identified the first paraganglioma of the vagus nerve, 24 and Birrell proposed the term vagal body tumor in 1953. 25 During the past decades, several case series have been reported VP with possible multifocality with other PGL and malignant potential. Its possible familial occurrence has been formally recognized after it has been made for carotid and jugular PGL.…”
Section: Discussionmentioning
confidence: 99%
“…Other areas, particularly those deeper in the tumour, may show predominantly fibrous tissue (Fig. X)-a common finding in both the carotid and vagal body tumours (Birrell, 1952(Birrell, , 1953. Again…”
Section: Fig VIII High Power Photomicrograph Of a Jugular Body Tumcmentioning
confidence: 91%
“…(Case 1 1 ) . (~3 8 0 ) Attempts were made with the material available, to demonstrate a "nerve supply" similar to that found in the carotid body tumour (Birrell, 1952). Some success has been achieved using Willis's (1954) been demonstrated, despite the close resemblance of the parenchyma of the tumour to It should be noted here that distant the normal body's parenchyma; previous experience has shown that one needs a fortunate section for this purpose.…”
Section: Pathological Aspectsmentioning
confidence: 96%